Assessment of Practices on Purchase of Packaged Foods and Utilization Patterns of Food Labels among Adults in Puducherry - Lalithambigai Chellamuthu; Premkumar Ramasubramani; Sadhvika Kanagat (Indian Journal of Community Medicine)
Background: There is an increase in the manufacture and consumption of prepackaged foods as a result of widespread urbanization, long working time, and adaption to a sedentary lifestyle. The majority of these prepackaged foods contain food labels. Food labeling is a community-based strategy that informs customers about a food’s nutritional composition, empowering them to choose healthier foods. To assess the practices on the purchase of packaged foods and utilization patterns of food labels among adults in Puducherry. Material and Methods: A cross-sectional survey in the field practice area of a private medical college at Puducherry was carried out for two months including adults residing for > 6 months in selected villages/wards. A sample size of 460 with a multistage sampling technique was considered. Data collection using a semi-structured questionnaire incorporated into Epi-collect software and was analyzed using SPSS16. Ethical clearance was obtained from Institutional Ethical Committee. Written informed consent was sought from participants. Results: Around 271 (58.91%) and 189 (41.08%) respondents were residing in urban and rural regions, respectively. Purchase of packages was seen in 297 (64.57%) people. Only one-fourth of the subjects had the practice of reading the food labels, with urban residents having a better practice when compared with rural population (P value < 0.05). Conclusion: The study reveals a low level of utilization pattern of food labels among consumers of packaged food products. The findings of this study would be helpful for concerned authorities in creating and improving awareness among consumers and ensuring that their usability is improved.